2018
DOI: 10.1097/ccm.0000000000002928
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Procalcitonin Guidance in Patients With Suspected or Confirmed Sepsis: A Systematic Review and Meta-Analysis*

Abstract: In adult patients with suspected or confirmed sepsis, procalcitonin guidance reduces antibiotics duration with no observed adverse effects on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 35 publications
3
52
0
2
Order By: Relevance
“…The use of PCT has been evaluated for the decision to stop antibiotic treatment. A recent meta-analysis confirms that PCT can be a feasible biomarker for the reduction of consumption and duration of antibiotics for septic patients (7). This has also been shown in newborns with early-onset sepsis (8).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The use of PCT has been evaluated for the decision to stop antibiotic treatment. A recent meta-analysis confirms that PCT can be a feasible biomarker for the reduction of consumption and duration of antibiotics for septic patients (7). This has also been shown in newborns with early-onset sepsis (8).…”
mentioning
confidence: 80%
“…Quantitative estimation of PCT is useful. Systemic infection (sepsis) is unlikely with PCT level of <0.5 μg/L . A level of 0.5–2.0 μg/L indicates possible systemic sepsis, 2.0–10.0 μg/L suggests that systemic infection (sepsis) likely and PCT levels of >10.0 μg/L indicate severe bacterial infection, almost always bacterial sepsis or septic shock.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A declining ProCT level in the first few days has been shown to be a predictor of mortal- ity [17,33]. A meta-analysis of 10 RCTs with 3489 patients demonstrated that ProCT monitoring with clinical evaluation resulted in a shorter duration of antibiotic use of about 1.5 days and demonstrated that ProCT use did not have a negative effect on mortality or duration of ICU stay [34].…”
Section: Procalcitonin and Sepsismentioning
confidence: 99%
“…Patients presenting to the emergency department with fever may present opportunities to improve antimicrobial usage by the addition of novel host-directed markers, such as procalcitonin (PCT), to clinical judgment and pathogendirected tests [2]. Although previous trials found PCT to decrease antibiotic usage and improve clinical outcomes in specific indications such as lower respiratory tract infection [3] and sepsis [4], the value of PCT in patients with fever without specified clinical syndrome has been understudied.…”
mentioning
confidence: 99%